Hubungan Indeks Massa Tubuh terhadap Dysmenorrhea pada Mahasiswi Fakultas Kedokteran Universitas Kristen Krida Wacana Angkatan 2015 - Budiman Hartono; Fallentino Christman Leuhery (Jurnal Kedokteran Meditek, 2020)
Overweight is a problem that is increasingOverweight is a risk factor for dysmenorrhea. The present study aimed to analyse the relationship between body mass index with dysmenorrhea of female students from batch 2015 in UKRIDA Medical Faculty. This is a cross sectional analytical correlation. Data were collected from June until December 2018 using questionnaire, microtaise to measure height, and scales to measure body weight. The average age of female students were 21 years old. Fifty-one students had normal body weight (48,2%). Of all respondents, 63 students (59,4%) reported pain (dysmenorrhea). The study found relationship between body mass index and dysmenorrhea among the students.